Laboratory studies on the influence of biomass particle size on pyrolysis and combustion using TG GC/MS. (15th September 2019) - Mlonka-Mędrala, Agata; Magdziarz, Aneta; Dziok, Tadeusz; Sieradzka, Małgorzata; Nowak, Wojciech
Highlights: Agriculture residues and energy crops combustion and pyrolysis were conducted. TGA analysis was used to study combustion and pyrolysis process kinetics. Kinetic parameters were determined. Particle size of biomass influences thermal process parameters. Abstract: The agriculture residues and energy crops have significant energy potential, which is not enough used so far. The agriculture production in Poland, and other countries of EU, gives a huge amount and variety of agriculture wastes. Whereas, energy crops characterise large annual growth at low-quality soil and high energy yields per unit of area. For this study three different agriculture biomass and two energy crops were selected. The samples were characterized in terms of their proximate and ultimate analysis. The main aim of this paper was to investigate the influence of biomass particle size distribution on the combustion and pyrolysis processes using thermogravimetric analysis (up to 600 °C at 5, 10 and 20 K/min or 50 K/min heating rate). Two fractions of biomass samples were investigated, smaller (S) size of major fraction smaller than 0.09 mm and sample of particle size smaller than 0.425 mm named larger (L). The gaseous products generated during pyrolysis process were analysed with GC/MS. Additionally, the kinetics analysis of studied processes was performed. Finally, it was found the particle size influences on the TG/DSC results and consequently significantly on the activation energy of combustion and slightly on pyrolysis of studied biomass samples.